Cross Mark Coordinate Determination and Automatic Registration for Offset Printing - Kasapoğlu, N. Gökhan; Gergin, Zeynep; Gençyılmaz, Mehmet Güneş; Torbalı, Ayşe Bilge; YÜKSEKTEPE, FADİME ÜNEY; GÜNDOĞDU, FATMA KUTLU (My University, 2018)
Offset printing is the method for producing commercialized printed media as newspapers and magazines. There are various factors contributing to the overall print quality such as; paper, ink pigment penetration, ink water balance, hygiene of environment, air temperature and humidity. Moreover, quality control is still operator dependent process where the operator is responsible for the visual checks of the printed material. One of the major checks applied is the correct registration of the plates in order to have a sharp image. The misregistration check may require more than one iterations creating setup time variation. Consequently, this highly time consuming setup takes considerable amount of time, especially in low circulation amounts. In this study a novel method called Cross Mark Coordinate Determination and Automatic Registration (CMCDR) is proposed for setup time reduction. CMCDR is based on x and y intensity profiles of registration marks and applied in a printing shop for automatic registration. For this purpose a traditional registration cross for overlapped color components (CMYK) as well as one registration cross for each individual color component is used to determine misclassification error. Using x and y intensity profiles of individual color component to determine misregistration errors and corrections of misregistrations are reduced with only one iteration.
Keywords: offset printing; printing quality; setup time; misregistration; automatic registration; image processing